PERANCANGAN KONSEP PENILAIAN KERJA UNTUK KEBUTUHAN ORGANISASI - Victorynie, Irnie; Fahrun, Elva; Ramadhan, Fajar; Irwansyah, Saripudin (Gapenas Publisher, 2024)
Job appraisal is a crucial component in human resource management that functions to evaluate employee performance while supporting strategic decision-making, such as promotion, training, and incentives. This study discusses the role, methods, challenges, and impact of job appraisal on employee productivity and development in organizations. The methods reviewed include 360-degree assessment and competency-based assessment, which have been proven to provide comprehensive evaluations and support individual competency improvement according to organizational needs. This study also identifies several key challenges, such as rater bias, lack of transparency, and employee resistance to the assessment process. To overcome these challenges, assessor training, the application of data-based technology, and open and inclusive communication are recommended strategic steps. In addition, employee involvement in the assessment process through discussion and two-way feedback has been shown to increase trust and participation in the evaluation process. The results of the study indicate that systematically and objectively designed job appraisals can significantly improve employee productivity, motivation, and development. In addition, effective job appraisals are an integral part of a sustainable human resource development strategy, encouraging the creation of an inclusive, collaborative work culture, and supporting the achievement of the organization's strategic goals.